Perlindungan Hukum bagi Pengemudi Gocar atas Pesanan Semu oleh Penumpang - Shafaa Istiana Nadzary; Retno Wulansari (Fakultas Hukum Universitas Islam Indonesia, 2025)
This research examines the legal protection provided for Gocar drivers against fake orders made by passengers and to identify possible legal remedies when losses occur. The main issues examined are the effectiveness of legal rules and partnership agreements in ensuring certainty and justice for drivers. The research employs a normative juridical method using statutory, contractual, and case study approaches, with data collected through literature review and analyzed qualitatively. The findings reveal that legal protection is actually regulated under the Indonesian Civil Code, the Consumer Protection Law, and the partnership agreement with PT Gojek Indonesia. However, in practice, such protection has not been effective since fake orders remain widespread, passengers often act in bad faith, and compensation mechanisms provided by PT Gojek are inadequate, leaving drivers to bear most of the losses. Steps that can be taken include settlement through PT Gojek’s internal system, dispute resolution via the Consumer Dispute Settlement Agency (BPSK), and civil lawsuits based on unlawful acts. The study concludes that existing legal protection remains weak, thus strengthening company policies and improving access to dispute resolution mechanisms are necessary to ensure more effective protection of drivers’ rights.